Volume Table Model and Inventory for Pinus caribaea in Madhya Pradesh - Pant, N. C. (Indian Forester, 2001)
Single tree volume tables for tropical pines (M.P.) have been prepared using the regression equation: Ln v = 0.0001715 + 2.312 Ln d. This was compared with other regression equations and was found most suitable and widely applicable. The results obtained were highly significant. Number of stems/ha, basal area and volume/ha were also calculated with confidence at 95% probability (P=0.05).